2020
DOI: 10.3389/fpls.2020.00581
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure-Activity Relationship of Humic-Like Biostimulants Derived From Agro-Industrial Byproducts and Energy Crops

Abstract: Structure-Activity Relationship for Humic-Lke Biostimulants can predict the bioactivity of lignin-derived HLS toward early growth of maize plants. The established QSAR may also be exploited to enhance by chemical techniques the bioactive properties of HLS and enhance their plant stimulation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 61 publications
0
30
0
1
Order By: Relevance
“…Biostimulants improve the antioxidant defense capacity of plants, which helps in stress tolerance. However, it is noticeable that there is a need for studies that indicate which mechanisms are responsible for this, a fact also observed by [ 77 ].…”
Section: Discussionmentioning
confidence: 96%
“…Biostimulants improve the antioxidant defense capacity of plants, which helps in stress tolerance. However, it is noticeable that there is a need for studies that indicate which mechanisms are responsible for this, a fact also observed by [ 77 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, little attention has been paid to using this biomass in nanoparticle form for agricultural purposes, other than as a support for released pesticide control [ 2 ]. In particular, very insufficient attention has been devoted to studying lignin biological properties and its derivative on crops, although recent research has highlighted its potential to stimulate crops [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increases in plant biomass ( Figure 3 and Figure 4 ) are in line with Nardi et al [ 65 ] and Savy et al [ 60 ] who found, that lignin derivatives positively influenced maize development, despite not affecting the germination. Positive effects on plant biomass can also be ascribed to the presence of guaiacyl and p-hydroxyphenyl groups into the lignin [ 53 ]. In particular, these two components can improve root system development and biomass [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, negative or contradictory effects are reported as well, including genotoxicity in blood lymphocytes, oxidative stress, and reduced offspring in Daphnia magna 19 21 . Only a few quantitative structure–activity relationships of humic substances have been conducted so far, but they showed that aromatic moieties and carboxyl/esterified functions have opposite effects in maize and Saprolegnia parasitica 14 , 22 . Although not directly transferable to fish, these results showed that the structure of the HS plays a tremendous role in its biological effects.…”
Section: Introductionmentioning
confidence: 99%